The dependent person, the family caregiver, and the resources used: A study with standard families - Rodrigues, Clara Maria da Noite Cota; Amaral, António Fernando Salgueiro; Tavares, João Paulo de Almeida (Journal of Nursing Referência, 2023)
Background: Demographic aging and the increase in chronic diseases are reflected in high levels of dependence for self-care. Objective: To characterize the Dependent Family member (FM), the Caregiving Family Member (CFM) and the resources used, in the context of classic families. Methodology: Quantitative and descriptive study. A Snowball sample was used. The “Families that Integrate Dependents in Self-care” form was used in 60 CFM.. Results: The FM are mostly female. Caregivers are predominantly elderly women with low education. The most basic care (e.g. feeding, giving drink and dressing are carried out with some ease by the CFM and are guaranteed. Care with a more differentiated intervention, such as performing exercises for the lower and upper limbs and activities to stimulate memory, do not are carried out. The main resource used is the health center. Conclusion: This study reveals the need for Family Nurses to intervene in family care at home through teaching and implementing more differentiated care (motor rehabilitation and cognitive stimulation), as well as promoting accessibility to care and health resources.